Jalaukavacharana Boon for Khalitya with special reference to Alopecia - An Outlook - Subhrajyoti, Chakraborty; Saniya , C K; Shalini (International Research Journal of Ayurveda & Yoga, 2024)
Face is an important and first attracting part of our body. Any flaws related to face or appearance can create physical as well as psychological problems in an individual. In recent years there has been increase in the incidence of hair problems in the tropical and developing countries like India due to various factors like pollution, stress, chemical treatments and medications etc. Hair loss is often distressing and can have a significant effect on one’s confidence. Hairfall termed as khalitya in Ayurveda. In Ayurveda it is mentioned under Shiroroga and Kshudraroga. Khalitya is commonly seen in the age group of 18- 40 years and most common in males than females. Khalitya is a slowly progressing disorder and it hampers the social life of an individual to a great extent. Now a days, Khalitya is mostly observed in youngsters due to their changing lifestyle, sleeping habits, unhealthy diets, stress and high use of chemicals on hairs. In Ayurveda there are number of medicines and oils which are beneficial for hair loss but it has been observed that medicine alone not able to give the visible results for hair fall. So to provide promising result application of Panchakarma like Virechan, Raktamokshan are helpful. Here special efforts have been made to show the beneficial sites of Jalaukavacharana in the form of Raktamokshan. Number of patients in kayachikitsa OPD of Sir Sundal Hospital, B.H.U were treated with Jalauka and got promising results in controlling hair fall. Thus the current article illustrates the role of Jalaukavacharana in hair fall.